DEVELOPMENT GEOMETRIC PATTERN OF PARADILA WEAVING NEED DESIGN INNOVATION - Agus Sukamto; Andri Setiawan (Universitas Sebelas Maret, 2017)
One center of Paradila woven fabric industry that produces woven sarong and band cloth with various motifs, there is geometric motif, mountains motif, flora and fauna motif. The woven fabric band songket and woven band songket batik is the latest product. This research aim to find out the motifs that exist in this woven fabric and the creation process. This research used the method of observation, interview and documentation. This method used to find out the development of geometric motif that have been created comprise line, dot, triangle, square, rectangle, rhomb and circle. The target of this research is to contribute and inspire and important innovation for the effort to build creative thinking and critical thinking, especially related to the development of geometric motifs based on the type of motif, arrangement of motif and the process of creation in woven this woven fabric so that the woven fabric become more interesting.